Peran Kepuasan Wisatawan Dalam Memediasi Pengaruh Promosi Media Sosial Dan Kualitas Pelayanan Pada Niat Berkunjung Kembali Ke Homestay Di Desa Kembang Kuning Lombok Timur - Elia Marta Tiana; Lalu Adi Permadi (Universitas Mataram, 2025)
This study aims to analyze the effect of Social Media Promotion and Service Quality on Revisit Intention with Tourist Satisfaction as a mediating variable in homestays at Kembang Kuning Tourism Village, East Lombok. This quantitative research employed Partial Least Square (PLS) analysis using data collected from 100 respondents who had stayed at Kembang Kuning homestays. The results show that social media promotion has a positive and significant effect on tourist satisfaction and revisit intention. Service quality also positively and significantly affects both variables. Tourist satisfaction significantly influences revisit intention and mediates the relationship between social media promotion and revisit intention but does not mediate the relationship between service quality and revisit intention. The R-square results indicate that tourist satisfaction is explained by social media promotion and service quality by 78.5%, while revisit intention is explained by 89.8%. These findings emphasize the importance of digital promotion and improved service quality in enhancing tourist satisfaction and fostering revisit loyalty.